The Objective Assessment of Cough Frequency in Bronchiectasis - Spinou, A.
Introduction: Cough in bronchiectasis is associated with significant impairment in health status. This study aimed to quantify cough frequency objectively with a cough monitor and investigate its relationship with health status. A secondary aim was to identify clinical predictors of cough frequency. Methods: Fifty-four patients with bronchiectasis were compared with thirty-five healthy controls. Objective 24-h cough, health status (cough-specific: Leicester Cough Questionnaire LCQ and bronchiectasis specific: Bronchiectasis Health Questionnaire BHQ), cough severity and lung function were measured. The clinical predictors of cough frequency in bronchiectasis were determined in a multivariate analysis. Results: Objective cough frequency was significantly raised in patients with bronchiectasis compared to healthy controls [geometric mean (standard deviation)] 184.5 (4.0) vs. 20.6 (3.2) coughs/24-h; mean fold-difference (95% confidence interval) 8.9 (5.2, 15.2); p < 0.001 and they had impaired health status. There was a significant correlation between objective cough frequency and subjective measures; LCQ r = −0.52 and BHQ r = −0.62, both p < 0.001. Sputum production, exacerbations (between past 2 weeks to 12 months) and age were significantly associated with objective cough frequency in multivariate analysis, explaining 52% of the variance (p < 0.001). There was no statistically significant association between cough frequency and lung function. Conclusions: Cough is a common and significant symptom in patients with bronchiectasis. Sputum production, exacerbations and age, but not lung function, were independent predictors of cough frequency. Ambulatory objective cough monitoring provides novel insights and should be further investigated as an outcome measure in bronchiectasis. © 2017, The Author(s).